Clinico-demographic Profile of Undifferentiated Inflammatory Arthritis Patients - Vaidya, Binit; Bhochhibhoya, Manisha; Joshi, Rakshya; Adhikari, Bhoj raj; Nakarmi, Shweta (Journal of Nepal Health Research Council, 2020)
Background: Undifferentiated inflammatory arthritis is a group of inflammatory joint diseases that do not fulfil the classification criteria for any other rheumatic or connective tissue disorders. This study aims to describe the clinical, demographic and serological features of undifferentiated inflammatory arthritis cases presenting at a tertiary level rheumatology centre from Nepal.Methods: A descriptive cross-sectional study conducted at National Centre for Rheumatic Diseases, Kathmandu, Nepal which represents a midterm analysis of the undifferentiated inflammatory arthritis registry maintained at the centre. Patients more than 18 years of age, who consented for the study having least one swollen or tender joint were enrolled. Ethical approval was obtained from Nepal Health Research Council.Results: A total of 1120 patients were enrolled in the study out of which 941 (84%) were females. The mean age at diagnosis was 46.0±12.8 years and most of them were in overweight range (mean BMI: 27.0±5.8) with 818 (73%) patients having BMI more than 24.0. Patients mostly had low disease activity at presentation (DAS 28 score of 2.5±0.8). Other markers of inflammation and patient reported outcome measures (health assessment questionnaire, patient global assessment and visual analogue scale) were also in the moderate range. Seropositivity for anti-citrullinated peptides and anti-nuclear antibodies was seen in 5 (0.45%) and 43 (3.8%) patients respectively. Majority of patients were non-smokers (77%). Inflammatory arthritis on musculoskeletal ultrasonography was seen in 638 (57%).Conclusions: Undifferentiated inflammatory arthritis was more common in overweight females. Serological markers and smoking status are not common features in these patients. Keywords: Early arthritis; Nepal; undifferentiated arthritis.